Parental Problem Drinking and Children’s Sleep: The Role of Ethnicity and Socioeconomic Status - Kelly, Ryan J. (J Fam Psychol, 2016)
We examined relations between mothers’ and fathers’ problem drinking and school-aged children’s sleep. Consistent with a health disparities perspective, children’s ethnicity and socioeconomic status were examined as moderators of relations between parental problem drinking and children’s sleep. Participants were 282 children (M age = 9.44 years) and their parents. Children were from diverse ethnic (65% European American, 35% African American) and socioeconomic backgrounds. Using a multi-informant design, parents reported on their own problem drinking and children’s sleep was assessed with actigraphs over 7 nights. After controlling for several influential covariates, moderation findings indicated that associations between heightened levels of parental problem drinking (predominately fathers’) and children’s shorter sleep duration, reduced sleep efficiency, and greater long wake episodes were most evident for African American children and those from lower socioeconomic backgrounds. Findings are among the first to establish relations between parental problem drinking and children’s sleep and indicate that not all children are at equal risk for sleep disturbances in such home environments. Results add to a growing literature that has examined children’s sleep within the family context and highlight the importance of considering the broader sociocultural milieu.